Recent Growth of Herbal Drug as Over-The-Counter Products - Mohammed Aadil Mansoori, Bharat Chouhan (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Herbal medicine has suddenly come into vogue with the notion of and quot; wellness and quot; becoming integral to the health-care business. However, here’s the catch. Although India is the birthplace of Ayurveda, one of the most popular forms of herbal medication, the domestic market looks positively anemic when compared with its healthy presence in the West. This review article describes that there are benefits and drawbacks to using herbal medications as over-the-counter (OTC) items. For many mild illnesses, they can be a safe and effective alternative to prescription medications, but the absence of control and standardization can be dangerous for consumer safety. To maintain the safe and efficient use of herbal medications as OTC products, it is crucial to encourage education and knowledge of their right usage.